Dasar Etis Alkitabiah Dalam Menghadapi Tantangan Moralitas - Brenda Kairupan; Marchya Djafar Djafar; Cinta Suku; Cintya Poluakan; Kanaya Tewu (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid development of globalization and advanced technologies such as artificial intelligence, Internet of Things, and genetic engineering have significantly altered human moral landscapes, intensifying moral relativism and creating ethical dilemmas. This study aims to identify key biblical ethical principles and analyze their relevance and application in addressing contemporary moral challenges. Employing a qualitative dominant mixed methods approach, the research integrates exegesis, quantitative surveys of 200 Indonesian Christians from diverse demographics, and semi-structured interviews with 15 theology and ethics experts. Data analysis involved thematic analysis supported by NVivo for qualitative data and descriptive statistics for quantitative data. Findings reveal that biblical ethics emphasizing love, justice, human dignity as Imago Dei, and stewardship provide a robust ethical foundation applicable to issues like digital ethics, bioethics, social justice, and environmental responsibility. The study also found strong community support for ethical AI use, data privacy, and active social justice engagement. The conclusion highlights that biblical ethics remain normative and prophetic, offering a holistic framework that guides moral transformation and social action. The research recommends integrating biblical ethical education within church and policy contexts to address modern dilemmas effectively.